PEWARISAN NILAI-NILAI KEARIFAN TRADISIONAL DALAM MASYARAKAT ADAT - Wijarnako, Beny (JURNAL PENDIDIKAN ILMU SOSIAL, 2013)
This study investigates how the inheritance of traditional values by the head of customs in the society. The study also sought to answer the question, how the tradition of leadership in the Kampung Dukuh? What is the form of traditional wisdom in the face of socio-cultural change kuncen and environmental change? Kuncen leadership is seen as a routine form of authority, because it is oriented to keep the line in the existing rules. Routine addition, the stability of traditional authority can be achieved due to internalized values, or the value of a strong process of socialization of traditional leaders in instilling values outhority sacred to the community. Kuncen is the guardian of the estate in the form of sacred tombs, traditions, and rules established by the ancestors; Within fungctions as kuncen protector also has a rule of customary law as chief at the time as a decision maker in solving the problem ofÂ  Kampung Dukuh community life.Keywords: Nilai Kearifan Tradisional, Masyarakat Adat, Peranan Kepala Adat